Chemical and physical properties of Sarawak (East Malaysia) rice straws - H, Nori; SA, Sani; Andrew Alek, Tuen (Elsevier, 2009)
Samples of straw from two varieties of rice, namely Biris and Saratani were collected and separated into leaf (including leaf blade and sheath) and stem fraction and were analyzed for chemical composition and predicted digestibility. The grain yield, straw yield, grain to straw ratio and leaf to stem ratio were determined in terms of dry matter.